1992
DOI: 10.3758/bf03334087
|View full text |Cite
|
Sign up to set email alerts
|

Rats counting rats: The use of conspecifics as discriminative stimuli

Abstract: Although a variety of experimental procedures have shown considerable evidence of "counting" in animals, there is no evidence of numerical competence when conspecifics are used as test stimuli. Here, we report evidence of a relative numerousness (2 vs. 4) judgment by rats that were required to discriminate the number of free-ranging conspecifics in an arena. This discrimination was ultimately disrupted by vigorous social interaction between the subjects and the to-becounted rats. Attempts to restrict the movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Such information can aid animals in determining which food patch they would visit (Beran et al, 2008). However, studies have shown that mosquitofish, rats, and female lions can make quantity judgments beyond foraging and involving social situations and communication between conspecifics (Davis and Bradford, 1986; Davis and Hiestand, 1992; McComb et al, 1994; Argrillo et al, 2007). This would allow individuals to determine the relative quantity of nearby individuals and use it to facilitate or deter interactions with these conspecifics (Kitchen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Such information can aid animals in determining which food patch they would visit (Beran et al, 2008). However, studies have shown that mosquitofish, rats, and female lions can make quantity judgments beyond foraging and involving social situations and communication between conspecifics (Davis and Bradford, 1986; Davis and Hiestand, 1992; McComb et al, 1994; Argrillo et al, 2007). This would allow individuals to determine the relative quantity of nearby individuals and use it to facilitate or deter interactions with these conspecifics (Kitchen, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research with rats has also indicated a high level of numerical competence. One early study [30] reported that rats could acquire the absolute numerousness concept of "two", and a more recent study [9] reported that rats acquired a relative numerousness concept. Other recent research has suggested much more sophisticated numerical cognition in rats.…”
Section: Introductionmentioning
confidence: 99%